Otherness as an educational response to social exclusion - Mínguez Vallejos, Ramón; Romero Sánchez, Eduardo; Gutiérrez Sánchez, Marta (Revista Complutense de Educación, 2018)
Exclusion is one of the sociological categories that best describes our times and, the economic crisis in which we are still immersed is reflected on it. If problems such as school failure and drop-out are not seriously tackled, educational exclusion will end up being synonymous with poverty and social exclusion. This idea is part of the concerns of institutions and agencies in educational policy both nationally and internationally. But these challenges and menaces that threaten education and society as a whole need to be solved by means of new approaches that address this problem more rigorously. It is essential to think of education from radically different presuppositions that make possible for the school context to cease to be a space of inequality production. Authors of this article start with Levinasian ethics and propose a model based on pedagogical otherness, so that the main aim is moving towards a less discriminatory and selective society. It is an ethic of compassion and responsibility that materializes in the “victims” recovery, in this case the excluded or dismissed. Educating for inclusion and equality necessarily involves responding to the other as a vulnerable and needy person. From this new perspective, the ethical dimension of education is reflected in a lifestyle guided by moral values both inside and outside of the classroom.
Keywords: education; exclusion; inclusion; equity; ethics; otherness